Socioeconomic characteristics of drivers versus pedestrians in pedestrian crashes - Antonio Giron; Xiaohan Gu; Robert J. Schneider (Transportation Research Interdisciplinary Perspectives)
This study of pedestrian crashes compares the home locations and socioeconomic characteristics of automobile drivers with the pedestrians who they struck. We collected driver and pedestrian sex, age, and home address from a random sample of 336 pedestrian crashes reported to police between 2011 and 2015 in the City of Milwaukee and the surrounding seven-county metropolitan region. We also gathered socioeconomic characteristics of driver and pedestrian home census tracts. Comparing the characteristics of drivers with the pedestrians they struck, it is most common for drivers and pedestrians to be from neighborhoods with similar income levels and similar race and ethnic characteristics. However, when looking at the crashes where drivers and pedestrians have different characteristics, several disparities are evident. Most prominently, adult drivers often crash into children, and drivers from higher-income tracts are more likely to crash into pedestrians from lower-income tracts than the reverse. Our results underscore the importance of efforts to create more equitable pedestrian safety outcomes, particularly for children and low-income pedestrians. Our approach provides a framework for future analyses of safety disparities between different transportation system users and socioeconomic groups.